Intimate relationships - Bradbury, Thomas N., ....-; Karney, Benjamin R., ....- (New York : W.W. Norton & Co., 2014)
A clear, balanced, contemporary look at how relationships work, from leading researchers in the field. As the first text to fully capture the excitement of today's research findings on couples, Intimate Relationships answers fascinating questions: How do relationships work?Why are they so hard sometimes?What are the principles that guide them?How can we use what we know to make them better?
Introduction : what do we want to know about intimate relationships? -- Tools for studying intimate relationships -- Theoretical frameworks for understanding intimate relationships -- Men and women, gay and straight -- Attraction and mate selection -- Individuals in relationships : personality and personal history -- Communicating closeness : how intimate relationships are maintained -- Managing differences : conflict and aggression -- Beliefs and values : thinking about intimate relationships -- Explanations and justifications : making meaning in intimate relationships -- Stress and social support : intimate relationships in context -- Interventions : making intimate relationships better -- Intimate relationships across the lifespan.
Includes bibliographical references and index.
Keywords: Interpersonal relations; Relaties -- Psychologie